2019
DOI: 10.1097/dss.0000000000001786
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Injection of Tranexamic Acid to Reduce Bleeding During Dermatologic Surgery: A Double-Blind, Placebo-Controlled, Randomized Clinical Trial

Abstract: BACKGROUND Topical application, oral and IV injection of Tranexamic acid (TXA) have been used to reduce surgical bleeding.OBJECTIVE To evaluate the safety and efficacy of TXA injected subcutaneously to reduce bleeding during dermatologic surgery.METHODS In this double-blinded, placebo controlled, randomized prospective study, 131 patients were randomized to subcutaneous injection of lidocaine 2% diluted 1:1 with either saline (placebo) or TXA 100mg/1ml prior to surgery. Before the second stage or closure, size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 29 publications
0
41
0
3
Order By: Relevance
“…We need to mention that, besides the fibrin, other agents used in the formulation may contribute to the haemostatic effect of our NFAH. Tranexamic acid is a procoagulant drug that has an antifibrinolytic action and has been successfully used to reduce blood loss in several types of surgery (Meng, Pan, Xiong, & Liu, ; Queiroz et al, ; Suh, Kyung, Han, Cheong, & Lee, ; Zilinsky et al, ). Indeed, it has been shown that the use of tranexamic acid and fibrinogen reduces blood loss and improves coagulation measurements in a porcine model of liver injury (Zentai et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…We need to mention that, besides the fibrin, other agents used in the formulation may contribute to the haemostatic effect of our NFAH. Tranexamic acid is a procoagulant drug that has an antifibrinolytic action and has been successfully used to reduce blood loss in several types of surgery (Meng, Pan, Xiong, & Liu, ; Queiroz et al, ; Suh, Kyung, Han, Cheong, & Lee, ; Zilinsky et al, ). Indeed, it has been shown that the use of tranexamic acid and fibrinogen reduces blood loss and improves coagulation measurements in a porcine model of liver injury (Zentai et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…A recent double‐blind placebo‐controlled trial in 131 patients suggested that intradermal injections of TA 100 mg/mL prior to dermatological surgery reduced bleeding, as assessed by the ratio of surgical wound size to bloodstain. Haemostasis was found to be subjectively enhanced in the TA group also ( P = 0.043), especially those on anticoagulant medications ( P = 0.01) …”
Section: Reduction Of Bleedingmentioning
confidence: 96%
“…Tranexamic acid is the most popular anti-fibrinolytic used in aesthetic surgery [48]. In our review, 23 studies assessed the use of TXA in various aesthetic or breast-related procedures [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64]. [57,59,60], and one was a case series [52].…”
Section: Aesthetic Surgery/breast Surgerymentioning
confidence: 99%
“…For topical/local administration, four studies reported topical administration either using soaked pledgets (undefined dosage) [52], soaked sponge tampons (undefined dosage) [57], or wound moistening with a 25 mg/ml TXA-saline solution [49,58]. In addition, three studies reported adding TXA to tumescent solution or local anesthetic solution [50,59,62].…”
Section: Aesthetic Surgery/breast Surgerymentioning
confidence: 99%
See 1 more Smart Citation